Does Top Management Support Improving The Quality of AIS? - Elza Fransisca; Yenni Carolina; Rapina Rapina (International Journal of Pertapsi, 2023)
There is extensive growth in Accounting Information System (AIS) utilization during the COVID-19 pandemic in order to adapt to this situation. Due to the great increase in the use of AIS, it is necessary to develop the quality of AIS itself to produce good quality accounting information for users. The accounting information system can be affected by many factors. This study aims to analyze the effect of top management support on the quality of the AIS. This research was conducted on fifty five private banks in Indonesia. The data was retrieved using a questionnaire distributed directly or online. This type of research is explanative research with a quantitative approach. There are two research results, namely: (1) top management support has a positive effect on the quality of the AIS, (2) the quality of the information system has a positive effect on the quality of accounting information.